Mask-Compliant Orthogonal Precoding for Spectrally Efficient OFDM - Ravinder Kumar; Khawar Hussain; R. López-Valcarce (IEEE Transactions on Communications, 2021)
Orthogonal precoding constitutes a powerful technique to reduce spectrum sidelobes of multicarrier signals. This reduction is bought at the cost of introducing precoder redundancy, which results in some throughput loss and additional precoding/decoding complexity. When the goal is to meet some spectral emission mask constraints, it is desirable to avoid unnecessary sidelobe suppression in order to keep precoder redundancy at a minimum. In this context, we introduce a general framework under which we develop a novel Lagrange multiplier-based mask-compliant orthogonal precoder design targeting minimal redundancy. We also adapt to this framework two previously proposed designs based on spectral notches and minimum out-of-band emission, respectively, to explicitly incorporate mask constraints. Simulation results are provided to show the effectiveness of the proposed designs under different practical masks for multicarrier wireless systems.
Keywords: rodin; spectrum shaping; winter